1999
DOI: 10.1210/jcem.84.6.5737
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Levels of Acid-Labile Subunit in Patients with Anorexia Nervosa1

Abstract: One of the observations in malnutrition is that serum insulin-like growth factor (IGF)-I levels are decreased, and this decrease is associated with an altered profile of IGF binding proteins (IGFBPs). In human circulation, IGFs are mostly present as an approximately 150-kDa ternary protein complex consisting of IGFs, IGFBP-3, and acid-labile subunit (ALS). In the present study, to clarify the effect of nutrition on serum ALS levels, we investigated 33 patients with anorexia nervosa. Serum levels of ALS were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…We found that subjects with a lower weight and BMI had lower serum ALS levels. Others have also demonstrated lower ALS levels after calorie restriction and in patients with anorexia nervosa [35]. These results indicate that nutritional status plays a role in the regulation of serum ALS levels.…”
Section: Discussionmentioning
confidence: 56%
“…We found that subjects with a lower weight and BMI had lower serum ALS levels. Others have also demonstrated lower ALS levels after calorie restriction and in patients with anorexia nervosa [35]. These results indicate that nutritional status plays a role in the regulation of serum ALS levels.…”
Section: Discussionmentioning
confidence: 56%
“…Низька маса тіла для даного гестаційного віку описана в дітей із мутацією ІФР-КЛС, але ми не знайшли кореляції між довжиною і масою тіла при народженні в [26,27]. Ці результати свідчать про те, що статус харчування відіграє певну роль у регуляції рівня КЛС у сироватці крові.…”
Section: таблиця 1 клінічні та лабораторні показники дітей із затримкою внутрішньоутробного розвитку та соматотропною недостатністюunclassified
“…Disease and catabolic state : Several studies demonstrate that ALS production is reduced during catabolic conditions Oster et al, 1995;Bereket et al, 1996;Lang et al, 1996;Frystyk et al, 1999;Fukuda et al, 1999;Moller et al, 2000;Kong et al, 2002a;Kong et al, 2002b). In humans, suffering from burn injury or cirrhosis, ALS synthesis is decreased (Frystyk et al, 1998;Moller et al, 2000).…”
Section: Regulation Of Alsmentioning
confidence: 99%